Reuse In Modelling Instructional Design - Chong, Hwee Reei (2007)
Instructional Design (ID) is a difficult task. Even when formal design methods may help in this task, most critical design decisions or knowledge remain undocumented making reuse a difficult task. Case-based scenarios, which contain captured data and knowledge during each ID instance, simulate real-life and provide a basis for reuse of best inherent knowledge in these scenarios to scaffold designers or instructors to reach better ID decisions and consequently to create learning materials, which meet diverse students' needs.